A Challenging Case of Miliary Tuberculosis in Pregnancy - Anuja Singh; Farha Siddiqui; Anand Kumar Maurya; Shashank Purwar; Saurabh Saigal (International Journal of Mycobacteriology)
Miliary tuberculosis (TB) is an uncommon yet severe condition that can pose substantial risks to pregnant women and their unborn child. This case study describes a 22-year-old pregnant female at 23 weeks of gestation presented with breathlessness, fever accompanied by chills, dry cough, and loss of appetite. With no significant comorbidities, her initial symptoms were inconclusive, leading to her initial diagnosis as a case of pyrexia of unknown origin. Despite receiving iron supplements for anemia and broad-spectrum antibiotics, her health continued to decline, prompting her transfer to a specialized medical center where advanced molecular testing ultimately confirmed a diagnosis of miliary TB. Upon admission, she was promptly started on anti-TB therapy and managed in the intensive care unit, where her clinical course included the development of acute respiratory distress syndrome (ARDS) requiring ventilatory support. Through meticulous monitoring and multidisciplinary intervention, the patient stabilized and ultimately delivered a healthy baby girl through normal vaginal delivery. Miliary TB, though rare, is challenging to diagnose during pregnancy due to overlapping symptoms with other conditions. This case underscores the critical importance of recognizing the atypical presentations of miliary TB in pregnant women, particularly in the context of previous exposure. It highlights the need for high clinical suspicion, timely diagnosis, and comprehensive management strategies to ensure favorable outcomes for both mother and child in the face of such challenging clinical scenarios.